ASSESSING DROUGHT IMPACTS IN ERBIL, IRAQI KURDISTAN: A STUDY OF LAND SURFACE TEMPERATURE AND VEGETATION HEALTH INDEX USING LANDSAT TIME-SERIES - Mohammad, Ragheb K.; Zaki , Sara H.; Gaznayee, Heman A. Ahmed; Sabr , Halmat A.; Aliehsan, Payman H.; Hammad, Sherwan Y.; Ababakr , Snoor H.; Razvanchy, Hawar A.; Hakzi, Kawa K. (Science Journal of University of Zakho, 2025)
Drought is a natural disaster that has severe implications for various aspects of society, including the economy, agriculture, environment, and community. The study conducted in the Erbil province, Kurdistan Region, Iraq from 1998 to 2017 aims to determine the frequency and intensity of drought, highlighting its diverse effects on society, encompassing the economy, agriculture, environment, and local community. Indicators, for instance, the Land Surface Temperature (LST) obtained from satellite data (Landsat) and the Vegetation Health Index (VHI), were employed to evaluate the severity of droughts. The outcomes indicated that Erbil encountered severe droughts in 1999, 2000, and 2008, which resulted in a significant decrease in crop outcomes. Additionally, 2008 was marked by escalating drought conditions, as measured by VHI values exceeding 40; as a result, the percentages reached (86.5%, 67.6%, and 53.7%), respectively. Significant relationships were revealed, with a confidence level of 0.9, between VHI and various factors such as precipitation, LST, and crop yield, with corresponding degrees of (-0.612, 0.615, 0.613, and 0.635). The study also disclosed that alterations and decreases in precipitation occur as the growing season progresses, whereas the following years (2000, 2008, and 2012) saw a pronounced decline in yield, failing to meet the lower limit of water demands for crops. Moreover, the most affected locations in Erbil Province were found to be in the central and southwestern parts of the province.